2015
DOI: 10.1016/j.biopsycho.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sighing on the cardiovascular system

Abstract: Elicitation of high-amplitude oscillations in the cardiovascular system may serve to dampen psychophysiological reactivity to emotional and cognitive loading. Prior work has used paced breathing to impose clinically valuable high-amplitude ~0.1Hz oscillations. In this study, we investigated whether rhythmical sighing could likewise produce high-amplitude cardiovascular oscillations in the very low frequency range (0.003–0.05Hz). ECG, respiration, skin conductance, and beat-to-beat blood pressure were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…The instructions given for a task are also an important consideration. In some cases, 116 , 117 , 118 researchers administer a low-demand cognitive ‘Vanilla' Task, 119 which may have some relevance for psychiatric populations that have difficulty sitting still or experience stress under experimental ‘resting-state' conditions. Instructions with attentional demands may also modulate HRV, primarily because of changes in respiratory depth and frequency.…”
Section: Ibi Collectionmentioning
confidence: 99%
“…The instructions given for a task are also an important consideration. In some cases, 116 , 117 , 118 researchers administer a low-demand cognitive ‘Vanilla' Task, 119 which may have some relevance for psychiatric populations that have difficulty sitting still or experience stress under experimental ‘resting-state' conditions. Instructions with attentional demands may also modulate HRV, primarily because of changes in respiratory depth and frequency.…”
Section: Ibi Collectionmentioning
confidence: 99%
“…However, this can bear the risk of "excessive" sighing that can override metabolic needs and lead to reduction in pCO 2 below optimal levels. Sighing also affects frequency oscillations in multiple cardiovascular parameters (Vaschillo et al, 2015); the implications of these effects remain to be explored. Addressing such questions has the potential to help us qualify the observed respiratory patterns as either detrimental or beneficial for the musicians.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…Sighing is associated with emotional states [44], such as is observed in states of anxiety where sighing is exaggerated [45]. Furthermore, evidence suggests that excessive sighing can exaggerate panic [45].…”
Section: Respiration and Sighingmentioning
confidence: 99%
“…For example, in experiments using mice that were genetically engineered to lack the ability to sigh, it was found that the mice incapable of sighing died of major lung problems sooner than normal mice [45] [46]. Additionally, research suggests that sighing helps to reset normal breathing patterns, and can "activate the cardiovascular system…by imposing very low frequency oscillations" [44]. These studies support our theory that breathing is vital to cellular functions and oscillatory activity that influence unconscious activities of the heart and lungs that involve emotions.…”
Section: Respiration and Sighingmentioning
confidence: 99%